Optimising location of unified power flow controllers by means of improved evolutionary programming - Hao, J.; Shi, L.B.; Chen, Ch (IEE proceedings. Generation, transmission, and distribution, 2004)
The unified power flow controller (UPFC) is one of the most promising Flexible AC Transmission Systems (FACTS) devices for the load flow control. Simultaneous optimisation of location and parameters for UPFCs is an important issue when the given number of UPFCs is applied to the power system with the purpose of increasing system loadability. This paper presents a mathematical model about optimal location and parameters of UPFCs to maximise the system loadability subject to the transmission line capacity limits and specified voltage level. An improved computational intelligence approach: self-adaptive evolutionary programming (SAEP) is used to solve the nonlinear programming problem presented above for better accuracy. Case studies of the IEEE 30- and 118-bus systems using the proposed model and technique demonstrate that the proposed mathematical model is corrective and efficient. Furthermore, steady-state performance of power system can be effectively enhanced due to the optimal location and parameters of UPFCs.